Multinational CGIAR-Support - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
An Interview with Dougou Keita, The Manager of AfDB's Agriculture and Agro-Industry Division on AfDB, CGIAR, and partners to develop platform to hasten delivery of improved agric technologies in Africa